2018
DOI: 10.1542/peds.2017-3046
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism and Iodine Deficiency in Children on Chronic Parenteral Nutrition

Abstract: Children on chronic PN are at risk for developing iodine deficiency and resultant hypothyroidism; hence, these children should be screened for these outcomes. Further studies are needed to define the temporal onset of iodine deficiency and timing to thyroid dysfunction related to PN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 17 publications
1
25
1
Order By: Relevance
“…In North America, iodine is not routinely included in PN [ 1 , 37 , 38 , 39 , 40 ], whereas European [ 3 , 7 ] and Australian [ 2 ] trace elements commercial solutions usually contain iodine.…”
Section: Trace Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In North America, iodine is not routinely included in PN [ 1 , 37 , 38 , 39 , 40 ], whereas European [ 3 , 7 ] and Australian [ 2 ] trace elements commercial solutions usually contain iodine.…”
Section: Trace Elementsmentioning
confidence: 99%
“…While some studies have revealed adequate iodine status under this dose [ 42 ], other authors claim it is not sufficient to meet the needs of children on PN [ 43 , 44 ]. There are pediatric reports of iodine deficiency and hypothyroidism described with iodine-free PN use [ 37 , 38 , 39 , 40 , 45 ], highlighting the importance of iodine substitution given its impact on neurodevelopment. Other authors have reported the absence of iodine deficiency despite absence of supplementation [ 42 ], likely secondary to adventitious iodine sources.…”
Section: Trace Elementsmentioning
confidence: 99%
“…Several reports [ 43 , 58 , 61 , 86 ] demonstrated significant selenium deficiency hypothyroidism, however, there are studies [ 42 , 60 ] in which hypothyroidism was associated with a significant increase in selenium serum levels. Furthermore, the larger set of studies [ 39 , 40 , 47 , 54 , 64 , 72 , 74 , 87 , 88 ] revealed no significant differences in the level of this element in patients with hypothyroidism compared to healthy controls. Although selenium and iodine are among the most intensively studied elements in the wide context of a number of thyroid diseases, some aspects of action of these elements in the thyroid gland still need to be elucidated.…”
Section: Resultsmentioning
confidence: 95%
“…All patients were required to have no underlying diseases, normal thyroid function by serological examination, and no taken of thyroid preparations or iodine-containing drugs recently. Exclusion criteria: (1) uneven thyroid density, with low-density lesions and calcification; (2) a history of thyroid surgery or thyroid artifacts seriously affected by the surrounding; (3) abnormal thyroid function. A total of 31 patients, aged 22-79 years, with an average age of 54.61±15.13 years, were enrolled in the study, including 16 males and 15 females.…”
Section: Subjectsmentioning
confidence: 99%